2020
DOI: 10.1590/0004-282x20200043
|View full text |Cite
|
Sign up to set email alerts
|

Spatial orientation tasks show moderate to high accuracy for the diagnosis of mild cognitive impairment: a systematic literature review

Abstract: Spatial disorientation has been observed in mild cognitive impairment (MCI) and is associated with a higher risk of progression to Alzheimer's disease (AD). However, there is no gold standard assessment for spatial orientation and paper-and-pencil tests lack ecological validity. Recently, there has been an increasing number of studies demonstrating the role of spatial disorientation as a cognitive marker of pathological decline, shedding new light on its importance for MCI. This systematic review aimed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…In our study, disorientation in time, place, and person was another important feature of aMCI. One study found that the mental-orientation task differentiated MCI and HCs with 95% accuracy [76, 77], and another study reported that orientation tasks were among the best individual items for distinguishing aMCI patients from HCs [78, 79]. The importance of orientation as an indicator of aMCI may be explained by hypoperfusion in the bilateral inferior parietal lobules, the bilateral superior parietal lobules, the posterior cingulated cortex, lateral orbitofrontal, bilateral medial orbitofrontal cortices, and precuneus [80].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, disorientation in time, place, and person was another important feature of aMCI. One study found that the mental-orientation task differentiated MCI and HCs with 95% accuracy [76, 77], and another study reported that orientation tasks were among the best individual items for distinguishing aMCI patients from HCs [78, 79]. The importance of orientation as an indicator of aMCI may be explained by hypoperfusion in the bilateral inferior parietal lobules, the bilateral superior parietal lobules, the posterior cingulated cortex, lateral orbitofrontal, bilateral medial orbitofrontal cortices, and precuneus [80].…”
Section: Discussionmentioning
confidence: 99%
“…TO presents a greater difference between subjects with MCI or dementia and those without impairment [ 66 ]. Other studies, however, have observed that deterioration of SO in MCI is associated with a higher risk of progression to AD [ 67 ] and spatial disorientation is common in AD [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, older people have difficulties walking and navigating in a new environment ( Lithfous et al, 2013 ; Lester et al, 2017 ), resulting in reduced wayfinding abilities. These changes are even more pronounced during the transition from healthy aging to cognitive impairment and dementia ( Gazova et al, 2012 ; Cohen and Verghese, 2019 ; Costa et al, 2020 ). They represent a high burden on older people and lead to fear of getting lost, social withdrawal, and a subsequent decrease in physical mobility ( Panel on Prevention of Falls in Older Persons, American Geriatrics Society and British Geriatrics Society, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies used experiments in virtual reality (VR) environments to assess spatial orientation ( Zakzanis et al, 2009 ; Kizony et al, 2017 ; Tascon et al, 2018 ; Costa et al, 2020 ; Paliokas et al, 2020 ). VR approaches are highly controlled but lack the dual-task characteristic of combining spatial navigation with walking.…”
Section: Introductionmentioning
confidence: 99%